The Gaia–ESO Survey: Membership probabilities for stars in 63 open and 7 globular clusters from 3D kinematics. Issue 2 (30th October 2021) - Jackson, R J; Jeffries, R D; Wright, N J; Randich, S; Sacco, G; Bragaglia, A; Hourihane, A; Tognelli, E; Degl'Innocenti, S; Prada Moroni, P G; Gilmore, G; Bensby, T; et al.
ABSTRACT: Spectroscopy from the final internal data release of the Gaia –ESO Survey (GES) has been combined with Gaia EDR3 to assign membership probabilities to targets observed towards 63 Galactic open clusters and 7 globular clusters. The membership probabilities are based chiefly on maximum likelihood modelling of the 3D kinematics of the targets, separating them into cluster and field populations. From 43 211 observed targets, 13 985 are identified as highly probable cluster members ( P > 0.9), with an average membership probability of 0.993. The addition of GES radial velocities successfully drives down the fraction of false positives and we achieve better levels of discrimination in most clusters over the use of astrometric data alone, especially those at larger distances. Since the membership selection is almost purely kinematic, the union of this catalogue with GES and Gaia is ideal for investigating the photometric and chemical properties of clusters as a function of stellar mass, age, and Galactic position.